Commodities at a Glance: Special Issue on Rare Earths - United Nations Conference on Trade; Development (United Nations, 2016)
The series “Commodities at a Glance” aims to collect, present and disseminate accurate and relevant statistical information linked to international primary commodity markets in a clear, concise and reader-friendly format. Data on Rare Earths are sparse and there is no dedicated international public institution that monitors the rare earth market to provide authoritative and objective statistics on the sector. As a result, this report has attempted to combine several sources of information in order to present the most possible accurate picture on the rare earths market.